2020
DOI: 10.18203/2349-2902.isj20202832
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of effectiveness of Mannheim peritonitis index scoring system in predicting the morbidity and mortality in peritonitis due to hollow viscous perforation

Abstract: Background: Peritonitis is defined as inflammation of the peritoneal cavity, caused by a number of etiologic agents including bacteria, fungi, viruses, chemical irritants, and foreign bodies. The Mannheim peritonitis index (MPI) is one of the simple scoring systems in use that allows the surgeon to easily determine outcome risk. Aims and objective: To estimate outcome of patients with perforation peritonitis. To evaluate effect of MPI score in identification of high risk cases.Methods: A prospective study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Results showed that 72% (80/111) of patients got discharged and 28% (31/111) exhibited mortality; the majority of mortality was in patients with MPI >29, and mortality increased in patients with higher MPI scores, similar to other studies [ 5 , 6 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…Results showed that 72% (80/111) of patients got discharged and 28% (31/111) exhibited mortality; the majority of mortality was in patients with MPI >29, and mortality increased in patients with higher MPI scores, similar to other studies [ 5 , 6 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…The majority of the patients, i.e., 84% (42/50), were discharged uneventfully, and the rest of the patients, i.e., 16% (8/50), expired. Different studies have recorded mortality rates ranging from 0% to 6% in the MPI <21 groups, 20% to 28.13% in the MPI 21-29 group, and 50% to 95.65% in the MPI > 29 groups [16][17][18][19][20]. In our study, out of the total mortality of eight patients, 62.5% (5/8) of the patients had an MPI score of >29, 23.1% (3/8) of the patients had an MPI score of 21-29, whereas there was no mortality in patients with an MPI score of 21 (Table 5).…”
Section: Discussionmentioning
confidence: 99%